Sintesis minyak goreng sehat (Diacylglycerol) - Tirto Prakoso; Danu Wicaksana; Roy Winarso; Tatang H. Soerawidjaja (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2007)
The syntesis of healty cooking oil (Diacylglycerol)Diglyceride I Diacylglycerol (DAG) oil is a compound resulting from the chemical bonding between glycerol and two free fatty acid molecules which follows a different metabolic route compared to triglyceride-type oils so that this type of oil does not cause fat accumulation in the body. This research isfocused at obtaining experimental evidence from the Archer-Daniels-Midland (2002) synthesis method, identifying the effect of the molar ratio between the reactants and reaction time on the DAG yield using the glycerolysis method, and at synthesizing a cooking oil with diglycerides as its major component. The diglyceride synthesis process in this research was done via glycerolysis with a varying glycerol : TAG ratio of 1:1, 3:2, 2:1 and 5:2. Reaction time was varied at 1 and 3 hours. The synthesis was undertaken at 190°C, using CH3COOK as catalyst at a dose of 1% of the mass ofTAG reactant. Experimental results indicate that longer reaction time increases the molar amount of diglycerides formed in the healthy cooking oil product. The molar ratio of glycerol to triglycerides which produces the highest DAG yield was 2:1, with a reaction time of 3 hours, which resulted in a yield of 97. 726%-mol DAG per mol TAG reactant. Higher molar ratio of glycerol to tryglycerides also increases the percentage of monoglycerides (MAG)formed.Keywords: DAG (Diglycerides), glycerolysis, TAG (Triglycerides) AbstrakMinyak Digliserida/Diacylglycerol (DAG) adalah senyawa hasil ikatan kimia antara g/iserol dengan 2 buah asam lemak bebas yang mengikuti jalur metabolik yang khas dan berbeda dengan jenis minyak trigliserida sehingga tidak menyebabkan penimbunan lemak dalam tubuh. Penelitian ini bertujuan untuk mendapat bukti eksperimental dari metode Archer-Daniels-Midland (2002), mengetahui pengaruh rasio mol reaktan dan waktu reaksi terhadap perolehan DAG dari metode gliserolisis dan mendapatkan hasil minyak goreng yang memiliki kandungan utama digliserida. Proses sintesa digliserida dalam penelitian ini dilakukan dengan reaksi gliserolisis yang menggunakan variasi rasio reaktan gliserol : TAG 1:1, 3:2, 2:1 dan 5:2. dengan dan variasi waktu 1 dan 3 jam. Sintesa ini berlangsung pada temperatur 190°C dan menggunakan katalis CH3COOK sebanyak 1% dari berat TAG yang digunakan. Hasil penelitian menunjukkan bahwa semakin lama waktu reaksi gliserolisis, semakin tinggi jumlah mol dig/iserida yang terbentuk di dalam minyak goreng sehat. Rasia mol reaktan gliserol: trigliserida yang menghasilkan perolehan DAG tertinggi adalah rasio 2:1 dengan waktu reaksi 3 jam, yaitu sebesar 97, 726%-mol DAG per mol TAG mula-mula. Semakin tinggi rasio mol reaktan gliserol : trigliserida, %-monogliserida (MAG) yang terbentuk juga semakin tinggi.Kata Kunci: DAG (Digliserida), gliserolisis, TAG (Trigliserida)